2022
DOI: 10.1155/2022/9073405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-Administration of N-Acetylcysteine and Vitamin E on Cyclophosphamide-Induced Ovarian Toxicity in Female Rats

Abstract: Cyclophosphamide is used to treat various types of cancer. However, it can reduce ovarian function and fertility rate. The current study was done to compare the effects of N-acetylcysteine and vitamin E on cyclophosphamide-induced ovarian damage. Thirty-five rats were randomly divided into 5 groups: control (C), cyclophosphamide (CP, 200 mg/kg single dose intraperitoneally), T1 (cyclophosphamide + vitamin E at 200 mg/kg), T2 (cyclophosphamide + 200 mg/kg N-acetylcysteine), and T3 (cyclophosphamide + N-acetylcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Garlic supplementation has been shown to reduce estrogen, progesterone, and luteinizing hormone (LH) levels, thereby reducing the hormonal imbalances that commonly occur in PCOS. Garlic has been found to contain compounds such as allicin , which may help regulate estrogen levels [ 73 , 77 , 78 ]. Modaresi et al reported that garlic can increase the secretion of estrogen and progesterone blood levels in women.…”
Section: Resultsmentioning
confidence: 99%
“…Garlic supplementation has been shown to reduce estrogen, progesterone, and luteinizing hormone (LH) levels, thereby reducing the hormonal imbalances that commonly occur in PCOS. Garlic has been found to contain compounds such as allicin , which may help regulate estrogen levels [ 73 , 77 , 78 ]. Modaresi et al reported that garlic can increase the secretion of estrogen and progesterone blood levels in women.…”
Section: Resultsmentioning
confidence: 99%
“…Cy lacks specificity in targeting the cell cycle, resulting in its toxicity to cells not actively undergoing division [27]. Cy also triggers inflammation, and the increased expression of cytokines facilitates programmed cell death by activating Yurttancikmaz/Ozcan/Tanoglu/Tok/ Timur/Cetin interferon alpha and gamma [28]. CYP2B and CYP3A activate Cy to produce 4-hydroxycyclophosphamide, which is eventually metabolized to phosphoramide mustard (PM) [29].…”
Section: Discussionmentioning
confidence: 99%
“…GSH supplementation or co-treatment with antioxidants significantly suppressed this effect [35]. Raeeszadeh et al [28] studied N-acetylcysteine, a precursor of GSH and vitamin E, on Cy-induced ovarian damage and demonstrated a synergistic protective effect. Other studies investigating the protective effects of 2-mercaptoethane sulfonate [20] and mirtazapine [36] against gonadotoxic medications have also revealed that preservation of antioxidant substances contributes to the preservation of ovarian function, like reduction of GSH depletion.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in cryogenics indicating that broccoli extract in a certain dose could improve serum and testicular oxidative biomarkers, testicular structure and function, and sperm quality before and after cryopreservation improving reproductive performance [ 27 , 28 ]. In addition, with regard to ovarian function, this can be reduced by using cyclophosphamide, but the simultaneous administration of N-acetylcysteine and vitamin E could significantly reduce the side effects of cyclophosphamide, especially in the ovarian tissue [ 29 ].…”
Section: Discussionmentioning
confidence: 99%